A first dedicated heart valve unit: safe and streamlined patient care for the rapidly growing field of transcatheter heart valve interventions. (14th October 2021) - Hell, M; Wirtz, V; Geyer, M; Kreidel, F; Jansen, T; Von Bardeleben, R S; Muenzel, T
Abstract: Background: A dedicated Heart Valve Unit was launched in 2018 to meet the demands of the growing transcatheter heart valve program by optimizing patient care in a single dedicated unit. Purpose: To assess the performance of the heart valve unit (all steps of patient care in a single unit with intermediate care facilities) over a conventional approach (preparation on a normal ward, postprocedural intensive care unit (ICU) monitoring and transfer to an additional monitoring ward before discharge) in a high volume center. Methods: Retrospective analysis including patients undergoing transcatheter mitral or tricuspid valve repair who were admitted to the Heart Valve Unit (02/2018–01/2020) compared to a conventional patient care approach (02/2016–01/2018). Patients who were already preprocedurally admitted to the ICU or in whom ICU monitoring postprocedurally was mandatory (direct annuloplasty, valve replacement) were excluded. The Heart Valve Unit patient care algorithm is presented in figure 1. We assessed procedural numbers, length of hospital stay, length and need for ICU monitoring, patient transfers between wards and periprocedural safety including in-hospital mortality. Results: We observed a 164% increase in procedures (521 vs. 316 in total, 369 vs 282 with mitral valve procedures and 152 vs 34 tricuspid valve procedures) with the launch of the Heart Valve Unit over the 2-year-interval compared to the earlier time period. Length of in-hospital stay was significantly decreased compared to a conventional approach (9±7 vs. 12±11 days, p<0.001). In particular, postprocedural stay could be shortened from 7±7 to 5±6 days (p<0.001). Patients were less transferred between different wards in the Heart Valve Unit setting (p<0.001). Whereas all patients were postprocedurally transferred to the ICU in the conventional setting, only 16% of patients required an ICU bed immediately after the procedure due to complex interventions, intraprocedural events or high-risk comorbidities. The length of stay on ICU declined from 1.4±1.4 to 0.5±2.2 days. Among the patients re-transferred to the Heart Valve Unit directly after the procedure, 2% (10 patients) required an ICU bed in the further course due to hemodynamic instability (2), severe bleeding (4), seizures (1), ventricular fibrillation (1), anaesthetic overhang (1) or after urgent surgery due to a atrioventricular fistula (1). After stabilization, all patients were re-transferred to the Heart Valve Unit and discharged hereinafter. There was no intra-hospital death among these patients. Conclusions: A dedicated Heart Valve Unit allows a safe and optimized patient care structure for transcatheter valvular interventions by combining all pre- and postprocedural steps in a single unit, thereby decreasing length of in-hospital stay to meet increasing economic demands. ICU capacity can be specifically used for complex procedures aftercare and complication monitoring. FUNDunding Acknowledgement: Type of funding sources: None.